Innovations in the system of economic security - Zinenko, K. А. (My University, 2022)
It has been proven that ensuring economic security is a necessary condition for the sustainable functioning and development of the enterprise's economic system in modern times. The introduction of innovations, which are an important means of increasing production efficiency, can guarantee the economic security of the organization and success in competition.
Інновації в системі економічної безпеки
Keywords: economic security; sustainable development; innovation; assessment; efficiency; enterprises